On some properties of dissipative functional differential inclusions in a Banach space - Obukhovskiĭ, Valeri; Zecca, Pietro (Topological Methods in Nonlinear Analysis, 2000)
For a semilinear functional differential inclusion of the form$$y'(t) \in Ay(t0+f(t, x_t)$$satisfying a dissipativity condition in a separable Banach space we provethe existence of a periodic solution and a global compact attractor.